Penggunaan Media Sosial Instagram dalam Pembentukan Corporate Branding - Tarisha Desmora Mahpudin; Siti Nursanti; Maulana Rifai (Jurnal Ilmiah Wahana Pendidikan, 2023)
This Research discusses the corporate branding built by the Karawang Regency Communication and Information Office on Instagram Social Media. The purpose of this research is to find out how the communication process carried out by the Karawang Regency Communication and Information Office and the obstacles experienced in building corporate branding on instagram social media. In this study, researchers used qualitative research methods with a descriptive approach and were supported by Harold Lasswell’s theoretical studies. The selection of informants was carried out using purposive sampling technique. The informants in this study totaled five people, with two people being main informants, and three people being supporting informants. Data acquisition in this study was carried out in several ways, namely observation, interviews, documentation, and literature studies. The results of this study indicate that the communication process carried out by Diskominfo Karawang Regency applies Harold Lasswell's theory, namely that a good way to explain communication is to answer the following questions: "Who Says What In Which Channel To Whom With What Effect" or "who conveys (source), what is conveyed (message), through what (channel), to whom (receiver), and what is the effect (effect)”. Then the obstacles experienced by Diskominfo Karawang consist of internal factors and external factors. The internal factor is the lack of adequate facilities and infrastucture that are not sufficient to support the activities of Diskominfo Karawang. While the external factor is for people who are less technologically literate, automatically the information shared is not evenly distributed as a whole because of the lack of the understanding of technology.